Validation of 18F–FDG-PET Single-Subject Optimized SPM Procedure with Different PET Scanners - Presotto, Luca; Ballarini, Tommaso; Caminiti, Silvia Paola; Bettinardi, Valentino; Gianolli, Luigi; Perani, Daniela (Neuroinformatics (Totowa, N.J.), 2017)
18 F–fluoro-deoxy-glucose Positron Emission Tomography (FDG-PET) allows early identification of neurodegeneration in dementia. The use of an optimized method based on the SPM software package highly improves diagnostic accuracy. However, the impact of different scanners for data acquisition on the SPM results and the effects of different pools of healthy subjects on the statistical comparison have not been investigated yet. Images from 144 AD patients acquired using six different PET scanners were analysed with an optimized single-subject SPM procedure to identify the typical AD hypometabolism pattern at single subject level. We compared between-scanners differences on the SPM outcomes in a factorial design. Single-subject SPM comparison analyses were also performed against a different group of healthy controls from the ADNI initiative. The concordance between the two analyses (112 vs. 157 control subjects) was tested using Dice scores. In addition, we applied the optimized single-subject SPM procedure to the FDG-PET data acquired with 3 different scanners in 57 MCI subjects, in order to assess for tomograph influence in early disease phase. All the patients showed comparable AD-like hypometabolic patterns, also in the prodromal phase, in spite of being acquired with different PET scanners. SPM statistical comparisons performed with the two different healthy control databases showed a high degree of concordance (76% average pattern volume overlap and 90% voxel-wise agreement in AD-related brain structures). The validated optimized SPM-based single-subject procedure is influenced neither by the scanners used for image acquisition, nor by differences in healthy control groups, thus implying a great reliability of this method for longitudinal and multicentre studies.